Everything That Is Old Is New Again—Old Again—New Again . . . - Paparozzi, Mario A. (Journal of contemporary criminal justice, 2018)
Since the decade of the 1970s, the policies and practices in probation, parole, and community corrections have vacillated between an emphasis on rehabilitation and enforcement, and most recently back to rehabilitation. While these paradigmatic shifts in ideology are driven by top management, generally at the behest of elected officials who are concerned with burgeoning costs and the desire not to appear soft on crime, it is what is done in everyday practice at the “street level” that determines if change actually occurs and is interpreted. This essay discusses probation and parole practices with regard to fluctuations in emphasis on the offender rehabilitation and law enforcement functions of probation and parole officers.